When Too Good Is Too Much: Social Incentives and Job Selection - Tommaso G. Reggiani; Rainer Michael Rilke (Institute of Labor Economics (IZA), 2020)
We analyze the effects of substitutability of social incentives on the labor supply of gigworkers (N=944) in a natural field experiment. In our treatments, we vary the proportion of the worker's wage that is donated to a social cause. Our experimental design allows us to observe the decision to accept a job (extensive margin) and different dimensions of productivity (intensive margin). The results show that when the worker has to donate small or moderate parts to a prosocial organization, labor supply on the extensive margin remains unaffected, but productivity on the intensive margin increases; when workers have to give larger portions of their wages, labor supply and productivity decrease. When workers have to donate parts of their wages to an antisocial cause, labor supply on the extensive and intensive margin is negatively affected. We discuss the implications of these results for the understanding of social incentives and corporate social responsibility on labor supply.
Keywords: C93; D23; M52; 330; social incentives; labor supply; CSR; field experiment